Analisa dan Evaluasi Kawasan Sungai Batang Jirak Guna Menanggulangi Banjir pada Kelurahan Pengambiran Kecamatan Lubuk Begalung Kota Padang - Leilany, Lili; Aisya, Rahma; Arsyad, Nadra; Sari, Afrilda (JURNAL RIVET, 2025)
Flooding is a frequent natural disaster in Padang City, particularly inPegambiran Village, Lubuk Begalung District. The Batang Jirak River is one of therivers that traverses the area and plays a crucial role in flood mitigation. This studyaims to analyze and evaluate the Batang Jirak River area for flood mitigation usingHEC-RAS software. The research method used is hydrological analysis and spatialanalysis using rainfall data, river discharge data, and spatial data of the river area.The HEC-RAS modeling results indicate that the Batang Jirak River is safe fromflooding with return periods of 2 years, 5 years, 10 years, 25 years, 50 years, and100 years, thus eliminating the need for further river redesign. Based on theanalysis, several recommendations can be made to prevent future flooding,including the need to educate the surrounding community to prevent waste fromentering the river and the need to clean the riverbed of mud to maintain the smoothflow of water.